Observational longitudinal multicentre investigation of acute pancreatitis (GOULASH PLUS): follow-up of the GOULASH study, protocol. Issue 8 (3rd September 2019) - Mikó, Alexandra; Erőss, Bálint; Sarlós, Patrícia; Hegyi Jr, Péter; Márta, Katalin; Pécsi, Dániel; Vincze, Áron; Bódis, Beáta; Nemes, Orsolya; Faluhelyi, Nándor; Farkas, Orsolya; Papp, Róbert; et al.
Abstract : Background: Acute pancreatitis (AP) is an inflammatory condition that can lead to late consequences. Recurrent AP (RAP) develops in 20% of patients and chronic pancreatitis (CP) occurs in 7%–12.8%. However, we do not have sufficient information to establish an evidence-based statement to define early CP, or how to prevent its development. Aim: The aim of this study was to understand the influencing factors and to determine which parameters should be measured or used as a biomarker to detect the early phase of CP. Methods/Design: This is an observational prospective follow-up study of the GOULASH-trial (ISRTCN 63827758) in which (1) all severity of pancreatitis are included; (2) patients receive only therapeutic modalities which are accepted by the evidence based medicine (EBM) guideline; (3) whole blood, serum and plasma samples are stored in our biobank; and (4) large amount of variables are collected and kept in our electronic database including anamnestic data, physical examination, laboratory parameters, imaging, therapy and complications. Therefore, this fully characterised patient cohort are well suitable for this longitudinal follow-up study. Patients' selection: patients enrolled in the GOULASH study will be offered to join to the longitudinal study. The follow-up will be at 1, 2, 3, 4, 5 and 6 years after the episode of AP. Anamnestic data will be collected by questionnaires: (1) diet history questionnaire, (2) 36-Item Short-Form Health Survey, (3) physical activity questionnaire and (4) stress questionnaire. Genetic tests will be performed for the genes associated with CP. The exocrine and endocrine pancreatic, liver and kidney functions will be determined by laboratory tests, stool sample analyses and imaging. Cost-effectiveness will be analysed to examine the relationship between events of interest and health-related quality of life or to explore subgroup differences. Conclusion: This study will provide information about the risk and influencing factors leading to CP and identify the most useful measurable parameters. Trial registration number: ISRCTN63396106